Pengendalian Risiko dan Optimalisasi Persediaan Bahan Baku pada Usaha Kecil: Pendekatan Metode FMEA dan EOQ - Yuliatin Ali Syamsiah; Dwi Sukma Donoriyanto; Isna Nugraha (Pusat riset dan Inovasi Nasional, 2023)
This research aims to increase the efficiency of raw material management in the Warmindo Sugar Pak Har UMKM business by considering possible risks, optimizing order sizes, and determining manufacturing order times. An approach using the FMEA (Failure Modes and Effects Analysis) method is used to systematically identify risks that can affect the availability of raw materials. Next, this research looks for the optimal solution by calculating the Economic Order Quantity (EOQ) to determine the economical order size. The first specific objective is to identify risks that may occur in procuring raw materials, while the second specific objective is to optimize order sizes in order to minimize storage and purchasing costs. The third step is to determine the optimal time to place an order for making raw materials in order to maintain a smooth production process and avoid stock shortages. The results of this research are expected to provide insight to Warmindo Sugar Pak Har MSMEs regarding the risks that need to be anticipated in procuring raw materials, provide recommendations regarding economical order sizes, and increase understanding regarding ordering time control. It is hoped that this research can contribute to the development of more effective and efficient raw material management strategies in the context of MSMEs.